Black and White Rodeo Shots / Indios Arabic Stage in Color / B & W Parade Shots (1948)
[00:00:00] Scenes from a rodeo in black-and-white. [00:01:45] Color footage of the Indio "Arabic Stage" [00:03:00] Color footage of a parade in Clovis, including Shriners [00:03:49] Footage of parade continues in black-and-white